The role of the three-dimensional ultrasound in uterine evaluation in patients with reproductive failure: A comparative study - Abdulrahman Yehia Elkashef; Hossam El-Din Shawki; Ahmed Sameer Sanad; Ahmad Ezz El-Din Mahran (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Background: Congenital Mullerian duct anomaly is a common cause of infertility, preterm labor, first trimester abortion. Its estimated percentage varies between 0.1% - 3% in the general population and between 3% to 38% in patients with recurrent spontaneous pregnancy loss or with infertility. The use of 3-D ultrasound with image reconstruction in the diagnosis of congenital uterine anomalies has already been described [1].  Objective: To test the validity of 3D ultrasound in the diagnosis of different anatomical and structural lesions of the uterus in patients presented with reproduction failure, taking the combined diagnostic laparoscopy & diagnostic hysteroscopy as a gold standard method for diagnosis.  Material and methods: Patients who came to our hospital with uterine structural anomalies, suspected by 2D ultrasound or Hysterosalpingogram (HSG), were subjected to 3D ultrasound before undergoing combined laparoscopy and hysteroscopy.  Results: This study included 42 patients selected from 463 cases that presented to Minia University Hospital, Egypt. Sensitivity of 3D Ultrasound was 100% for Double system, submucous fibroid, Subseptae uterus, Unicornuate uterus, Bicornuate uterus, Arcuate uterus. As regards Asherman's syndrome it was 50% sensitivity , As regards polypi it was 67% While the specificity of 3D Ultrasound was: 100% in Double system, Subseptae uterus, Unicornuate uterus, Bicornuate uterus, Asherman's syndrome, polypi . As regards Arcuate uterus it was 95.2%, As regards Submucous fibroid it was 92%. The age of patients ranged from  21-35 years (mean age 28.4±4.3), 52.4% of the patients had primary infertility while 47.6% had secondary infertility.  Conclusion: Three Dimensional Ultrasound is a reliable diagnostic tool in cases of reproductive failure; it is superior to HSG in the diagnosis of all intracavitary lesions or anomalies, but not yet superior to laparoscopy & hysteroscopy.